Zambrano Alava,Dayanara Michelle (2023)GESTIÓN INTEGRAL DE RESIDUOS SÓLIDOS EN LA CIUDADELA SAN MIGUEL DEL CANTÓN EL EMPALME.Quevedo.UTEQ.146p. - Zambrano Alava , Dayanara Michelle (2023)
The management of solid waste has been a challenge due to the large amount of waste that citizens produce, if not handled properly, can have a negative impact on the health of people and the environment, in addition it is a commitment of both government and communities. The research was carried out with the objective of evaluating the integral management of solid waste in the San Miguel citadel of the El Empalme canton. The study begins with a diagnosis of the current management of solid waste, which was carried out through surveys, to know their perception of the current situation. 72 samples were taken for quantitative characterization in the homes of families, where the generation of daily per capita was 0.64 kg per inhabitants per day and with the composition of solid waste, the most generated was organic with 64.88%, 10.72% plastic waste, 10.01% metals, 7.98% paper / cardboard and 6.41% glass, causing accumulation of the same and spreading pollution. Through direct observation, the articles of the regulations that the inhabitants of the study area do not comply with were established. With the results obtained, a plan of good environmental practices was designed, which contains programs to be executed in the San Miguel citadel, to promote responsible consumption and implement the use of waste to obtain an economic benefit within the San Miguel citadel of the El Empalme canton.